Large wood in river restoration: A case study on the effects on hydromorphology, biodiversity, and ecosystem functioning. Issue 1 (23rd January 2022) - Anlanger, Christine; Attermeyer, Katrin; Hille, Sandra; Kamjunke, Norbert; Koll, Katinka; König, Manuela; Schnauder, Ingo; Nogueira Tavares, Claudia; Weitere, Markus; Brauns, Mario
Abstract: Large wood (LW) is an integral part of natural river ecosystems and determines their ecological integrity by modulating hydromorphology and providing habitats. Hence, LW installations are a common restoration measure in large rivers, even if effects on biodiversity are ambiguous or unknown for ecosystem functioning. Here we quantified the hydromorphological, biological, and functional effects of LW 8 months after installation in a large gravel‐bed river. Both morphological and flow diversity increased strongly by 821% and 127%, respectively. Similarly, fish abundance increased nearly 10‐fold, and macroinvertebrate diversity increased by 35%. Ecosystem functions benefited from LW installation and increased significantly (e.g., by up to 390% for bacterial production) at sites influenced by LW compared to those without LW. Our results highlight the role of the bark habitat of LW that increased the direct effects of LW via the provision of new habitat and stimulated ecosystem‐wide processes. Our integrative approach evaluating the success of LW installations in a large river revealed cascading effects from the provisioning of new habitats, the increase of species diversity to higher ecosystem functioning. It also demonstrated that hydromorphological parameters or community composition alone are insufficient to quantify the complex effects of LW installation, which underlines the necessity to evaluate restoration success with different measures.